The Top Management Triangle in Voluntary Hospitals (I) - Gordon, Paul (Academy of Management Journal, 1961)
Part I. Deals with a study on problems of organization in hospitals and the relationships among trustees, administrators and doctors. Approaches to the problems; Classifications of selected hospitals; Unique feature of organization in the hospital setting; Relationship of affiliation with teaching institutions.